Odpowiedzi

2009-11-28T12:02:18+01:00
5x + 6y = 1,5
-x +3y = 6

5x + 6y = 1,5
x - 3y = -6

x= -6 + 3y
5x + 6y = 1,5

5(-6 + 3y) + 6y = 1,5
-30 + 15y + 6y = 1,5
21y = 1,5 + 30
21y = 31,5/21
y = 1,5
x = -6 + 3y
x= -6 + 3*(1,5)
x= -6 + 4,5
x = - 1,5


y = 1,5
x= -1,5
2009-11-28T12:03:23+01:00
5x+6y=1,5
-x+3y=6 /*(-1)

x-3y=-6
5x+6y=1,5

x=-6+3y
5(-6+3y)+6y=1,5

x=-6+3y
-30+15y+6y=1,5

x=-6+3y
21y=31,5/:21

y=1,5
x=-6+3*1,5

y=1,5
x=-6+4,5

y=1,5
x=-1,5
2009-11-28T12:11:31+01:00
5x + 6y = 1,5
-x +3y = 6

5x + 6y = 1,5
x - 3y = -6

x= 3y -6
5x + 6y = 1,5

5(3y -6) + 6y = 1,5
15y - 30 + 6y = 1,5
21y = 31,5
y = 1,5
x = 3y -6
x = 3(1,5)-6
x = 4,5 - 6
x = -1,5

x = -1,5
y = 1,5

Spr.
5(-1,5) + 6(1,5) = 1,5
-(-1,5) +3(1,5) = 6

-7,5 + 9 = 1,5
1,5 + 4,5 = 6

1,5 = 1,5
6 = 6